GPCR-induced calcium transients trigger nuclear actin assembly for chromatin dynamics - Ying Wang (Nature Portfolio, 2019)
The extracellular cues regulating filamentous actin formation in somatic cell nuclei are unclear. Here, the authors show that activated GPCR signalling initiates transient accumulation of nuclear F-actin/formation in nuclear actin filaments, driven by calcium and requiring the nucleator Formin INF2.